Women’s Empowerment and Its Determinants in Bangladesh: Evidence from a National Survey - Sen, Kanchan Kumar; Nilima, Shahnaz (Dhaka University Journal of Science, 2018)
The potential factors associated with women‟s empowerment in household decision making as well as attitudes toward wife beating were determined in the study. The Bangladesh Demographic Health Survey (BDHS), 2014 data were used to get the determinants of women‟s empowerment. To measure the women‟s empowerment, the principal component analysis was used in the study. The ordinal logistic regression model was applied to determine the potential factors for women‟s empowerment. Results were also compared with the results obtained from classical linear regression model. The study revealed that lower difference of spousal ages and lower number of daughters were more likely to increase women‟s empowerment. Similar to other studies, early marriage and living in rural area gave the women lower empowerment but education, 1-4 family members, having at least one child, exposed to media, belonging to NGO and working outside home had greater positive influence on women‟s empowerment. Dhaka Univ. J. Sci. 66(2): 129-134, 2018 (July)